Functional indicators of a decline in the noradrenergic locus coeruleus in ageing: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Hammerer, Dorothea; Hopkins, Alexandra; Ludwig, Mareike; Yi, Yeo‐Jin; Lüsebrink, Falk; Liu, Kathy; Femminella, Grazia Daniela; Betts, Matthew J; Callaghan, Martina F; Howard, Robert J; Düzel, Emrah
Abstract: Background: Postmortem studies show that the locus coeruleus (LC), the major source of cortical noradrenergic projections, exhibits evidence of neurodegeneration early in Alzheimer's disease (AD). Indeed, the noradrenergic system is more affected than the dopaminergic or cholinergic ones. Albeit to a smaller extent, neuronal loss in the LC is also seen in cognitively normal older adults, which can in some cases reflect the earliest stages of AD neuropathology before cognitive changes are clinically detectable. These postmortem findings have been corroborated in recent years by in vivo assessments of LC integrity using anatomical MRI (magnetic resonance imaging) approaches. Before measurable neuronal loss occurs, functional LC decline should be observable. I will present the results of a series of studies involving pupillometry, high‐resolution fMRI (functional) as well as cognitive paradigms targeting noradrenergic function, which investigated whether a decline in LC function can be detected in cognitively normal older adults. Method: We examined LC function during an emotional memory task known to rely on the noradrenergic system in 22 healthy younger adults (18‐30 years) and 22 healthy older adults (62‐83 years) with pupillometry (a proxy for LC function) (Study 1), as well as 22 healthy younger adults (20‐31 years) and 28 healthy older adults (65‐84 years), using high resolution fMRI (Study 2). Result: Our studies reveal both, a) evidence for a decline in functional LC responses with ageing (Figure 1, pupillometric data), as well as, b) evidence for no decline in functional LC responses in older adults (in pupillometry and fMRI). Specifically, reduced LC responses with ageing were observed in experimental conditions that allowed for a more selective assessment of LC function, independent of the engagement of other brain areas, underlining the need for a careful selection of cognitive paradigms when investigating functional indicators of LC decline. Conclusion: Our results show that fMRI and pupillometry are promising methods for assessing changes in LC function in ageing and early AD. We provide recommendations for cognitive paradigms, experimental setups as well as data analysis methods for researchers interested in assessing functional changes in the noradrenergic system in AD and other disorders.